Improving fire retardancy of medium density fiberboard by nano‐wollastonite. (1st June 2020) - Esmailpour, Ayoub; Taghiyari, Hamid R.; Ghorbanali, Mohammad; Mantanis, George I.
Summary: The improving effects of addition of nano‐wollastonite on some fire properties of medium‐density fiberboard (MDF) were studied in this work. Nano‐wollastonite was added at four levels (2%, 4%, 6%, and 8%). The size range of at least 70% of nano‐wollastonite particles were 30 to 110 nm. The results showed statistically significant improving effect of nano‐wollastonite on time to onset of ignition. The improving effect was primarily attributed to an increase in thermal conductivity of board containing nano‐wollastonite. This increase in turn resulted in better curing of resin, and a higher integrity of fibers thereof. Moreover, nano‐particles provided a surface with reduced combustibility and therefore, penetration of fire to the inner layers of boards was delayed, thus improving fire properties. High and significant correlations were found between thermal conductivity coefficients of boards with different fire properties. It was concluded that for applications where fire properties are of prime importance, nano‐wollastonite content of 8% can be recommended. Moreover, further studies are needed to compare and standardize the results obtained from the apparatus used here with those obtained from internationally recognized apparatuses like cone calorimeter.